Inventory Of Seagrass Types In Talise Waters, Best Likupang District, North Minahasa, North Sulawesi - Paramitha Gracela Wakkary; Gaspar D. Manu (Sam Ratulangi University, 2022)
Seagrasses are the only group of flowering plants (Angiosperms) that live permanently in shallow coastal waters and play a key ecological role. Seagrasses are widely distributed in coastal waters around the world where the substrate and depth are suitable for growth. This research was conducted in the waters of Talise Island, Tambun Village, North Minahasa Regency, North Sulawesi Province. carried out using the cruising survey method. The data taken was carried out when the water conditions were in the dead moon phase, where the water experienced the lowest receding. Overall, 5 species of seagrass were found.Keywords: Seagrass; ecological role; Talise Island.AbstrakLamun (seagrass) adalah satu-satunya kelompok tumbuhan berbunga (Angiospermae) yang hidup secara tetap di lingkungan perairan pantai yang dangkal dan merupakan kunci dalam peranan ekologis. Lamun tersebar luas di perairan pantai di seluruh dunia yang substrat serta kedalaman cocok bagi pertumbuhannya. Penelitian ini dilaksanakan di Perairan Pulau Talise, Kampung Tambun, Kabupaten Minahasa Utara, Provinsi Sulawesi Utara. dilakukan dengan menggunakan metode survei jelajah. Data yang diambil, dilakukan pada saat kondisi perairan pada fase bulan mati, dimana air mengalami surut terendah. secara keseluruhan ditemukan jenis-jenis lamun sebanyak 5 spesies.Kata kunci: Lamun; Peranan ekologis; Pulau Talise.